Peri-Implant Microbial Signature Shifts in Titanium, Zirconia and Ceria-Stabilized Zirconia Reinforced with Alumina Sites Subjected to Experimental Peri-Implantitis: A Preclinical Study in Dogs - Roberto López-Píriz; David Sevillano; Manuel Fernández Domínguez; Luis Alou; Natalia González; Lidia Goyos-Ball; Belén Cabal; José Serafín Moya; María Luisa Gómez-Lus; Ramón Torrecillas (MDPI AG, 2024)
This study evaluates the dynamic shift in the microbiota at the peri-implant site of titanium (Ti) and zirconia (Zr) implants subjected to experimental peri-implantitis (PI) and, for the first time, of implants made of ceria-stabilized alumina-reinforced zirconia (Ce-TZP/Al), a revolutionary zirconia that is set to play a key role in modern implant dentistry. One- and two-piece (TP) implants, including Ce-TZP/AL TP/G3 glass, were placed bilaterally (six implants/side) in five beagle dogs to mimic a natural vs. ligature-induced PI following a split-mouth design. The experiment spanned 30 weeks from tooth extraction. Both PI models promoted plaque deposition at peri-implant sites. Comparatively, the PI induced by ligatures favored the deposition of anaerobes (p = 0.047 vs. natural). Regardless of the model, the plaque deposition pattern was entirely dependent on the implanted material. Ligated Ti and Zr implant sites accumulated up to 2.14 log CFU/mL unit anaerobic load (p ≤ 0.033 vs. non-ligated implant sites), predominantly comprising obligate anaerobes. Naturally occurring PI induced the deposition of co-occurring networks of obligate anaerobes and less oxygen-dependent bacteria. PI induction favored the enrichment of Ti and Zr sites with bacterial taxa belonging to the orange and red complexes (up to 28% increase naturally and up to 71% in the ligated hemiarch). Anaerobic deposition was significantly lower in ligated Ce-TZP/Al implant sites (p ≤ 0.014 vs. TI and Zr) and independent of the induction model (0.63-1 log units of increase). Facultative bacteria prevailed at Ce-TZP/AL sites. The abundance was lower in the Ce-TZP/AL TP implant. Unlike Ti and Zr sites, taxa from the orange and red complexes were negligible. Biofilms configured at the Ti and Zr sites after ligation-induced PI resemble those found in severe IP. We hypothesize that, although surface properties (surface energy and surface roughness) and physicochemical properties of the substrate play an important role in bacterial adhesion and subsequent plaque formation, Ce-TZP/Al modulates several biological activities that preserve the integrity of the gingival seal by limiting PI progression. In conclusion, biofilm progression differs in peri-implant sites according to the specific properties of the material. Ce-TZP/A, unlike titanium or zirconia, prevents dysbiosis in sites subjected to experimental PI and preserves the microbial signature of emergent obligate anaerobes related to PI development.